STRATEGI PENGEMBANGAN SMART CITY MELALUI PENYEDIAAN WIFI PUBLIK DI KOTA BANDAR LAMPUNG - Ros Mila; Meiliyana Meiliyana; Simon Sumanjoyo Hutagalung (Dialogue : Jurnal Ilmu Administrasi Publik, 2026)
The development of information and communication technology has encouraged local governments to adopt the Smart City concept in an effort to improve the quality of public services. One form of Smart City implementation in Bandar Lampung City is the provision of public WiFi services in open public spaces managed by the Communication and Informatics Office. The presence of public WiFi is expected to expand digital access and support community activities in the fields of communication, education, and economic development, although its implementation still faces several challenges. This study aims to analyze the development strategy for public WiFi provision in supporting Smart City initiatives in Bandar Lampung City and to identify the obstacles encountered in its implementation. The research employs a qualitative approach, with data collected through observation, interviews, and documentation involving government officials and public WiFi users, particularly in the Pulau Pasaran area. Data analysis was conducted using the Public Value Strategic Triangle framework, which includes the dimensions of public value, legitimacy and support, and operational capacity. The findings indicate that the provision of public WiFi has generated tangible public value, particularly in supporting access to communication and digital information, educational activities, and the economic activities of Micro, Small, and Medium Enterprises (MSMEs). The program is supported by an adequate policy framework; however, it still faces challenges related to budget limitations, infrastructure quality, and the capacity of technical human resources. Therefore, it can be concluded that the development strategy of public WiFi in Bandar Lampung City has functioned adequately but is not yet optimal and still requires further strengthening to support sustainable Smart City development.